The Impact of Corporate Social Responsibility on Customer Loyalty - Milena Stanisavljević (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
In this paper the impact of corporate social responsibility (CSR) dimensions on customer loyalty was researched. There are three main goals of this research: to show if the customers heard about the CSR, to emphasize the significance which customers gave to certain dimensions of CSR and to show that perceptions about CSR dimensions had the influence on customer loyalty. CSR is a possibility for company's differentiation, only if customers value these efforts. CSR is explained through the concept of the Pyramid of CSR. A socially responsible company needs to be dedicated to profit making, law obedience, ethical business management and to be a good citizen. The data was gathered using questionnaires; descriptive and regression analysis were carried out. The results showed that the majority of respondents heard about CSR term. Respondents perceived legal and economic dimension of CSR as the most important. There was an impact of the perceptions of CSR dimensions on customer loyalty, especially of philanthropic and economic dimensions. Based on the presented results, management recommendations could be given in order to help defining business strategy which could help in satisfying the interests of customers and to gain their loyalty.
Keywords: M14; M31; 330; corporate social responsibility; loyalty; strategy; management